Atlas: standard diagnostic tests for an unusual fracture. Issue 3 (25th February 2005) - Leigh-Smith, S; Price, R; Summers, D
Abstract : The case is reported of an unusual atlas fracture with no reports of such an injury in the literature. The diagnosis of this injury emphasises the importance of simple clinical decision instruments, and systematic interpretation of investigations.